What defines success when visions compete: lessons from post-Katrina New Orleans. Issue 4 (2nd October 2017) - van Dijk, Terry; Weitkamp, Gerd
ABSTRACT: Visions can be valuable tools for guiding and uniting land use interests in a region with fragmented administration. What determines the strength of a vision and how can it effectively play its role? Our study tested and supplemented hypotheses on the success factors of visions. We chose a city in a rebuilding process because that represents a most intensive and pressing vision process. We interviewed local policy-makers, designers, researchers, and journalists to find out what they would spontaneously cite as a vision's most crucial factors. We also reviewed the subsequent New Orleans recovery plans and compared our findings with hypotheses from visioning literature. The interviewees' spontaneous answers largely confirm the key hypotheses about success from the visioning literature. However, the most frequently mentioned factors were not in the literature: a vision needs to be propagated by a powerful authority, a favourable larger political climate, and the funds to sustain the implementation process. For a vision to make a difference, it needs to be substantively relevant and persuasive but also have a favourable institutional climate to help it along.